Ilmu Ma’ani dan Peranannya dalam Tafsir - Abdul Rohman; Wildan Taufiq (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2023)
This article is about ījāz, iṭnāb and musāwah in Qur’an, all three are part of tha ma’ani scinece of balaghah. The purose of writing this article is to find out the meaning of îjâz, ithnâb, dan musâwah and how it is applied in the verse of the Qur’an and what meaning it gives. The method used in this paper uses a qualitative method, sourced from written literature, ulûm Al-Quran, balâghah, tafser books, with a descriptive analysis approach, with decipter, analyze and describe it. The results obtained are that what is meant by îjâz in the study of ma’ani science is a sentence structure in which many meanings are collected and stated in a short editorial clearly and eloquently; ithnâb is the opposite it is adding a lafazh over a meaning for a specific purpose and it has seven forms. Meanhile what is meant by musâwah is disclosure of sentences whose meaning is in accordance with the number of words and the number of words according to the breadth of meaning, no addition or subtraction. Each gives different meaning implications according to the context of the conversation and the will of the speaker of kalam. The purpose of their use is also different, provide an in depth explanation and in the context of the Qur’an verse is to provide a proof that the verse of the Qur’an is the Kalam Allah SWT.